Low gestational age is associated with less anastomotic complications after open primary repair of esophageal atresia with tracheoesophageal fistula - Carmen Dingemann; Julia Brendel; Julia Wenskus; Sabine Pirr; Nagoud Schukfeh; Benno Ure; Konrad Reinshagen (BMC, 2020)
Abstract Background The aim of this study was to evaluate anastomotic complications after primary one-staged esophageal atresia (EA) repair relating to the patients` gestational age (GA). Methods Retrospective data analyses of patients who underwent closure of tracheoesophageal fistula (TEF) and primary esophageal anastomosis from 01/2007 to 12/2018 in two pediatric surgical centers. Exclusion of EA other than Gross type C, long-gap EA, minimal invasive or staged approach. Postoperative complications during the first year of life were assessed. Associated malformations, the incidence of infant respiratory distress syndrome (IRDS) and intraventricular bleeding were analyzed. Results Inclusion of 75 patients who underwent primary EA repair. Low GA was associated with significantly lower incidence of anastomotic complications (p = 0.019, r = 0.596, 95% CI 0.10-0.85). Incidence of anastomotic leakage (0% vs. 5.5%; p = 0.0416), recurrent TEF (0% vs. 5.5%; p = 0.0416) und anastomotic stricture (0% vs. 14.5%; p = 0.0019) was significantly lower in patients < 34 gestational weeks. Incidence of IRDS (55% vs. 0%; p < 0.0001) and intraventricular bleeding (25% vs. 3.6%; p = 0.0299) was significantly higher in patients < 34 gestational weeks. Conclusions Despite prematurity-related morbidity, low GA did not adversely affect surgical outcome after primary EA repair. Low GA was even associated with a better anastomotic outcome indicating feasibility and safety of primary esophageal reconstruction.